Psychometric Analysis of the Quarantine Coping Strategies Scale (Q-COPE) in the Spanish Language - Denis Frank Cunza-Aranzábal; Wilter C. Morales-García; Jacksaint Saintila; Salomón Huancahuire‐Vega; Percy G. Ruiz Mamani (My University, 2022)
The possibility of facing an epidemic or pandemic resulting in mandatory isolation or quarantine has become a relevant construct for comparing and evaluating coping strategies under such conditions. The objective of this research was to develop and analyze the psychometric properties of a scale to assess quarantine coping strategies (Q-COPE). This was an instrumental study and 1110 Peruvian adults (M = 26.9 years; SD = 9.77) participated in the context of social isolation. For the construction of the scale, qualitative and quantitative procedures were followed. The internal structure was evaluated by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The content analysis by expert judges supports the representativeness of the items related to the construct. EFA and CFA allowed the establishment of five factors: Emotional regulation, Information, Accommodation, Social support, and Altruism. The first-order model presents adequate goodness-of-fit indices: χ2 = 489.048, df = 220, χ2/df = 2.223, SRMR = 0.025, CFI = 0.969, TLI = 0.965, RMSEA = 0.047. Likewise, the second order model presented similar values: χ2 = 499.674, df = 225, χ2/df = 2.221, SRMR = 0.026, CFI = 0.969, TLI = 0.965, RMSEA = 0.047. The 23-item version was consistent with the proposed theory, obtained adequate fit indices and acceptable factor loadings (>0.70), and presented good internal consistency indexes evaluated by Cronbach’s α, ordinal α, omega (ω), and H coefficient. It is concluded that the Q-COPE scale presents good psychometric properties that justify its use in an adult population and allows the assessment of the coping strategies that people use in the face of a quarantine situation.
Keywords: Confirmatory factor analysis; Structural equation modeling; Cronbach's alpha; Psychology; Exploratory factor analysis; Coping (psychology); Goodness of fit; Construct validity; Population; Clinical psychology; Psychometrics; Social psychology; Applied psychology; Statistics; Medicine; Environmental health; Mathematics; Confirmatory factor analysis; Structural equation modeling; Cronbach's alpha; Psychology; Exploratory factor analysis; Coping (psychology); Goodness of fit; Construct validity; Population; Clinical psychology; Psychometrics; Social psychology; Applied psychology; Statistics; Medicine; Environmental health; Mathematics; Adaptation, Psychological; Adaptation, Psychological; Adaptation, Psychological; Adult; Adult; Adult; Humans; Humans; Humans; Language; Language; Language; Psychometrics methods; Psychometrics methods; Psychometrics methods; Quarantine; Quarantine; Quarantine; Surveys and Questionnaires; Surveys and Questionnaires; Surveys and Questionnaires; Reproducibility of Results; Reproducibility of Results; Reproducibility of Results; Social Sciences Psychology Clinical Psychology COVID-19 and Mental Health; Social Sciences Psychology Clinical Psychology Resilience and Mental Health; Social Sciences Psychology Social Psychology Stress and Burnout Research